Proliferation activity and hormonal status of atypical hyperplasia and endometrioid adenocarcinoma of the endometrium - P. V. Savchenko; I. S. Shponka; P. O. Hrytsenko; O. A. Savchenko (Zaporozhye State Medical University, 2024)
Atypical hyperplasia of the endometrium is a precancerous condition for endometrioid adenocarcinoma of the endometrium, which is the largest group among malignant neoplasms of the uterine body, according to the Cancer Registry, the mortality rate from which took the 3rd place in 2021. The absence of specific clinical manifestations complicates diagnostics at the early stages of the process, which necessitates the study of histological and immunohistochemical criteria to verify the diagnosis. The aim of the study. To improve the differential diagnostic morphological and immunohistochemical criteria for the diagnosis of atypical hyperplasia and endometrioid adenocarcinoma of the endometrium, using the latest international classification data. Materials and methods. Retrospective analysis of 76 cases of postoperative material of women for the period from 2020 to 2022 with a diagnosis of "endometrioid adenocarcinoma of the endometrium" - 61 cases and "endometrial hyperplasia with atypia" - 15 included an assessment of histological, immunohistochemical features, followed by statistical processing of the obtained results. Results. The incidence of endometrioid adenocarcinoma of the endometrium and atypical endometrial hyperplasia occurs in the premenopausal and menopausal periods. The expression level of the Ki-67 marker is directly proportional to the degree of tumor malignancy (p < 0.05). Estrogen receptors decrease as the degree of tumor malignancy increases. Progesterone receptors are equally present in endometrioid adenocarcinomas and atypical endometrial hyperplasia (p < 0.05). Conclusions. The necessity of using the Ki-67 marker and determining the hormonal status in endometrioid adenocarcinomas of the endometrium and atypical hyperplasia of the endometrium is argued.